2012
DOI: 10.3396/ijic.v8i4.035.12
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of surgical site infection in a tertiary health institution in Kano, Northwestern Nigeria

Abstract: Surgical site infection (SSI) is the most common complication following surgical procedures. The aim of this study was to determine the incidence and associated risk factors of surgical site infection in a tertiary health institution in Kano, Nigeria.The study was carried out between January 2008 and December 2010. Data was collected in a predesigned questionnaire forms which focused on demographic details, socioeconomic background and lifestyle while the diagnosis, surgical procedure, duration of surgery, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
34
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 12 publications
10
34
1
Order By: Relevance
“…The finding was similar to studies done in India 20.09% [21], Nigeria 20.3% [22], India 21.66% [23] and Egypt 22.6% [24]. But, lower compared to studies done in Tanzania 26% [5], India 33.5% [25] and Mekele, Ethiopia 75% [11].…”
Section: Discussionsupporting
confidence: 86%
“…The finding was similar to studies done in India 20.09% [21], Nigeria 20.3% [22], India 21.66% [23] and Egypt 22.6% [24]. But, lower compared to studies done in Tanzania 26% [5], India 33.5% [25] and Mekele, Ethiopia 75% [11].…”
Section: Discussionsupporting
confidence: 86%
“…The SSI, globally, is considered as a challenging problem that was facing all surgical patients who are acutely ill. The annual incidence rate of SSI in general population was 20.3% in Nigeria [4], 16% in India [5], and 14.7% in Japan [6]. The annual incidence rate of SSI in Jordan among Coronary Artery Bypass Graft Surgery (CABG) patients reached up to 16.8% [7].…”
Section: Introductionmentioning
confidence: 99%
“…In this study patients more than 50 years of age got infected, which was in contrast to other studies. [10] In the present study surgical site infection was significantly associated with contaminated class of wounds, being the highest (60%) for contaminated surgery, 33.3% for clean-contaminated surgery and 6.6% for clean surgery. While Mundhada AS [4] documented 17.65% clean and 39.39% clean contaminated wound were infected and Lilani et al [7] found 3.03% clean and 22.41% were clean-contaminated surgeries.…”
Section: Discussionmentioning
confidence: 74%